Nano Online 2016
DOI: 10.1515/nano.11671_2015.210
|View full text |Cite
|
Sign up to set email alerts
|

Textures on the surface of BSA films with different concentrations of sodium halides and water state in solution

Abstract: The formation of the textures on the surface of the films from the solutions of bovine serum albumin (BSA) with sodium halides (NaF, NaCl, and NaBr) of various concentrations was studied. The formation of symmetric zigzag textures on the surface of BSA films (Cryst Eng 3:173-194, 2000) in the presence of sodium halides depends on the conformational state of the protein globule. Thermal denaturation of BSA also did not allow to form zigzag textures on the surface of the films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 3 publications
(3 reference statements)
2
6
0
Order By: Relevance
“…In previous studies we found that zigzag (hexagonal) patterns [16][17][18][19], similar to those observed in [20,21], are formed on films obtained from saline solutions of native DNA or protein. For a quantitative description of this type of texture, we introduced the value L specific , which corresponds to the total length of zigzag patterns per unit area.…”
Section: анализ характеристик зигзагоподобных паттерновsupporting
confidence: 58%
See 4 more Smart Citations
“…In previous studies we found that zigzag (hexagonal) patterns [16][17][18][19], similar to those observed in [20,21], are formed on films obtained from saline solutions of native DNA or protein. For a quantitative description of this type of texture, we introduced the value L specific , which corresponds to the total length of zigzag patterns per unit area.…”
Section: анализ характеристик зигзагоподобных паттерновsupporting
confidence: 58%
“…The analysis was carried out on the basis of data obtained during the previous experiments [18,19,22,23]. The films were obtained from saline BSA solutions via vacuum drying at 40 °C in 20x20x1 mm 3 glass cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations